Sifat Sifat Mekanik Beton dengan Menggunakan Fiber Reinforced Polymer (FRP) - Ashad, Hanafi; Hartawan Nurdin, Rezki Muhammad Suharto; Nizar, Muhammad Chairus; Utina, Toni; Syarif, Muhammad (Universitas Batanghari Jambi, 2024)
This study investigates the impact of Carbon Fiber Reinforced Polymer (CFRP) reinforcement on the mechanical properties of concrete, by testing the compressive strength, tensile strength, flexural strength, and shear strength of concrete with and without CFRP reinforcement. The results of the study show a significant improvement in all aspects after the application of CFRP. Specifically, the compressive strength of concrete consistently increases after CFRP reinforcement, with CFRP 2 Layer reinforcement showing the highest increase. Similarly, the tensile strength and flexural strength of concrete also experience significant improvement after CFRP reinforcement, indicating better resistance to compression and tension. Lastly, CFRP reinforcement has a significantly positive impact on the shear strength of concrete, with an increase of up to 123% after the application of CFRP 2 Layers. These results indicate a substantial potential for improving the performance of concrete structures through the use of CFRP, with the greatest improvement observed in shear strength.